Effectiveness of a structured behavioural communication intervention programme in enhancing adherence amongst outpatients with mental illness at Tara Outpatient Clinic: a randomised prospective descriptive study - Lutaaya, Diana Sheila (My University, 2020)
Background Poor adherence amongst patients with mental disorders continues to pose a major treatment challenge in psychiatry. Despite the presence of innovative agents with fewer disabling side effects, patients’ failure to comply with their prescribed medication causes failure of the expected benefits Objectives An adherence study was undertaken at the Tara outpatient clinic in collaboration with the South African Depression and Anxiety Group (SADAG). The study explored the socio demographic factors associated with non-adherence and helped to determine whether a short message service (SMS) based intervention program would be useful in improving clinic attendance and medication adherence. Results The study showed that daily treatment reminders via SMS may not have enhanced overall adherence to treatment however it did manage to arrest the decline in adherence. It also showed a decline in adherence in the ‘treatment as usual’ group whereas there xi was no change in adherence in the treatment group. It found a significant relationship between substance use disorder and adherence. There was a decline in adherence in those with a substance use disorder in the ‘treatment as usual’ group, whereas the treatment group showed no change in adherence. Conclusion The SMS adherence program did not improve adherence rates but did stabilize attrition rates. An effective adherence program may decrease the rates of relapse and readmission and will in the long term decrease the burden of disease on our health care services.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020